Superapps: At the crossroads of enhanced customer experience and innovation management theories - Balogh, Attila; Varga, János (Edelweiss Applied Science and Technology, 2024)
This study focuses on one of the most notable digital innovations in recent times - the SuperApps, which synergically combine customer service, mobile usability, and integrated service offerings. Utilizing a comprehensive review of existing literature, this research explores the concept of the SuperApp, evaluates the feasibility of establishing a ranking system for SuperApps, and constructs a definitive top ten list of leading applications. Following this, the research advances to a primary investigative task, which entails a thorough analysis of academic sources to assemble and define the essential attributes that define a SuperApp, specifically revealing what essential features distinguish a mobile application as a SuperApp. To achieve these objectives, the study rigorously processes scientific articles available in the Scopus and Web of Science database, aiming to enhance the academic understanding and categorization of SuperApps within the digital technology domain. Using a bibliometric mapping methodology, which involves analysing keyword occurrences through VOSViewer, the conducted research identifies a notable academic gap in Scopus- and Web of Science-indexed documents. The analysis indicates that despite the prevalence of recent articles and academic texts, the defining characteristics of a SuperApp (commonly referred to as ’Super-App’ in Scopus-indexed scholarly literature) remain inadequately explored and understood. This gap underscores the need for further empirical research to clarify the features and implications of SuperApps. Such research could enrich the body of knowledge in the above-described documents, contributing to a more comprehensive understanding in the field. Based on experiences with Scopus and Web of Science by selecting some of the most cited articles from Google Scholar, this study has compiled a six-element list that encapsulates the most crucial characteristics of SuperApps. These fundamental features are then briefly analysed and presented, linked to some of the most impactful innovation management theories linked to SuperApp concepts also presented. This offers a comprehensive understanding of their significance and functionality within the SuperApp framework.